A critical review of scoring options for clinical measurement tools. (December 2015) - Avila, Maria; Stinson, Jennifer; Kiss, Alex; Brandão, Leonardo; Uleryk, Elizabeth; Feldman, Brian
Abstract Background The aim of this paper is twofold: (1) to describe the fundamental differences between formative and reflective measurement models, and (2) to review the options proposed in the literature to obtain overall instrument summary scores, with a particular focus on formative models. Methods An extensive literature search was conducted using the following databases: MEDLINE, EMBASE, PsycINFO, CINAHL and ABI/INFORM, using "formative" and "reflective" as text words; relevant articles' reference lists were hand searched. Results Reflective models are most frequently scored by means of simple summation, which is consistent with the theory underlying these models. However, our review suggests that formative models might be better summarized using weighted combinations of indicators, since each indicator captures unique features of the underlying construct. For this purpose, indicator weights have been obtained using choice-based, statistical, researcher-based, and combined approaches. Conclusion Whereas simple summation is a theoretically justified scoring system for reflective measurement models, formative measures likely benefit from the use of weighted scores that preserve the contribution of each of the aspects of the construct.